Publication rate for funded studies from a major UK health research funder: a cohort study. Issue 5 (2nd May 2013) - Turner, S; Wright, D; Maeso, R; Cook, A; Milne, R
Abstract : Objectives: This study aimed to investigate what percentage of National Institute for Health Research (NIHR) Health Technology Assessment (HTA) Programme-funded projects have published their final reports in the programme's journal HTA and to explore reasons for non-publication. Design: Retrospective cohort study. Setting: Failure to publish findings from research is a significant area of research waste. It has previously been suggested that potentially over 50% of studies funded are never published. Participants: All NIHR HTA projects with a planned submission date for their final report for publication in the journal series on or before 9 December 2011 were included. Primary and secondary outcome measures: The projects were classified according to the type of research, whether they had been published or not; if not yet published, whether they would be published in the future or not. The reasons for non-publication were investigated. Results: 628 projects were included: 582 (92.7%) had published a monograph; 19 (3%) were expected to publish a monograph; 13 (2.1%) were discontinued studies and would not publish; 12 (1.9%) submitted a report which did not lead to a publication as a monograph; and two (0.3%) did not submit a report. Overall, 95.7% of HTA studies either have published or will publish a monograph: 94% for those commissioned in 2002 or before and 98% for those commissioned after 2002. Of the 27 projects for which there will be no report, the majority (21) were commissioned in 2002 or before. Reasons why projects failed to complete included failure to recruit; issues concerning the organisation where the research was taking place; drug licensing issues; staffing issues; and access to data. Conclusions: The percentage of HTA projects for which a monograph is published is high. The advantages of funding organisations requiring publication in their own journal include avoidance of publication bias and research waste.